Study the Using of Reed Mats in Asphalt Pavement Layers - Lamia Abdul Jaleel Ahmed; Ammar Fakhir Sabri (Civil Engineering Journal, 2018)
During the service life, the asphalt pavement layers subjected to various detrimental types of distresses such as permanent deformation, fatigue, stripping and shoving which lead to the complete failure of the pavement. In Iraq roads the permanent deformation (rutting) is the importance distresses which cause impact on the highway performance and reducing the service life of the pavement. The research aims to utilize locally available materials and environment friendly as reinforcement layer. The program of this research include preparing asphalt mixes represent surface layer by using locally available materials and using the reinforcement layer which made of reed. The permanent deformation test has been done with three temperatures (40˚C, 50˚C and 60˚C) and four locations of the reed mats. The test results of the wheel- Track for the rutting measurement showed that the rut depth decrease in reinforcement layers as compared with unreinforcement layers for all temperature testing. The reed netting embedded bottom and middle of wearing layer has the best amount of improvement (75%, 84% and 85%).